BREAST IMPLANT-ASSOCIATED ANAPLASTIC LARGE CELL LYMPHOMA IN LI-FRAUMENI SYNDROME: CASE-BASED LITERATURE REVIEW - Sonagli, Marina; Guatelli, Camila Souza; Formiga, Maria Nirvana da Cruz; Abdala Junior, Joel; Bittencourt, Almir Galvão Vieria; Makdissi, Fabiana Baroni (Mastology, 2019)
Breast implant-associated anaplastic large cell lymphoma is a rare disease related to chronic seroma around breast implants. Breast implant-associated anaplastic large cell lymphoma has been recently recognized by the World Health Organization as a type of T-cell non-Hodgkin lymphoma of the breast. The main features comprise chronic seroma which develops a year posterior to breast surgery, with symptoms such as breast pain, swelling, skin hyperemia and a nodule or mass of the breast. Li-Fraumeni Syndrome is associated with germline TP53 mutation and enhances the risks of developing many types of cancers, including breast and hematologic malignancies. We report a case of a 56-year-old female with Li-Fraumeni Syndrome and a history of breast cancer who underwent a mastectomy to treat breast cancer and prophylactic contralateral nipple-sparing mastectomy followed by bilateral breast implant reconstruction with textured silicone implants. This patient developed Breast implant-associated anaplastic large cell lymphoma seven years later. A literature review on multidisciplinary approach to this condition was performed.